Cartografia social e organização política das comunidades remanescentes de quilombos de Salvaterra, Marajó, Pará, Brasil - BARGAS, Janine de Kássia Rocha (Universidade Federal do Pará, 2017)
Before 1988, the demands of Black rural communities were diluted in the agenda of social struggles of wider categories such as rural workers. With the promulgation of the Constitution, the emergence of the term “remaining Quilombo communities” gave rise to a specific set of demands.  In this scenario, the role of social scientists in the production of expert reports and academic works became a central aspect in the discussion of perceptions about the term “Quilombo”. Taking this into consideration, we analyze the experience of researchers from the New Social Cartography of the Amazon project (PNCSA, in portuguese) and their social relations with Salvaterra’s Quilombo communities, Marajó Island, Pará, who participated in workshops for the production of maps which resulted in a booklet entitled Quilombolas da Ilha de Marajó: Pará. We aimed at investigating, based on data collection and field research, how the relations between the cartography actors became political tools in the struggle for the latter’s social-territorial rights and their political organizing following the social cartography process. We point out that the social relations between the PNCSA and the Quilombo communities are characterized, on the one hand, as means for questioning the historical forms of disrespect and injustice and as mechanisms of politicizing the Quilombo social movement. On the other hand, as affirmation and academic consolidation of the Project’s research practice.